"I love foreigners' attitudes towards life": Reproducing lifestyles in an Iranian English language teaching context. Issue 5 (3rd September 2017) - Mirhosseini, Seyyed-Abdolhamid; Sazvar, Azam; Rashed, Farnoosh
Abstract: An important aspect of learning a foreign language is encountering the sociocultural orientations associated with it. The present qualitative study focuses on an Iranian setting of English language teaching (ELT) to explore the potential reflection and reproduction of certain cultural attitudes and lifestyles in this context. A total of 200 hours of 10 ELT classes with 62 students were observed and/or recorded in 4 months, and 20 teachers and students were interviewed. Based on a grounded theory approach, the bodies of data were explored through coding procedures and the emerging thematic structure was used to illustrate aspects of the possible reproduction of lifestyles. The context of concern appeared to provide a potential arena of naturalising aspects of imported lifestyles associated with the foreign language. Although students show various extents of adherence to their own culture, prolonged involvement in ELT discursive practices may contribute to the subtle alteration of their lifestyle orientations.